A lncRNA signature of tumor-infiltrating macrophages is associated with prognosis and tumor immunity in lung adenocarcinoma. (September 2022) - Guo, Yanhua; Li, Guofeng; Xu, Mingming; Peng, Bin
Abstract: Accumulating evidence suggests that long noncoding RNAs (lncRNAs) play a critical role in regulating cancer immunity and the tumor microenvironment. Tumor-infiltrating macrophages are one of the most abundant constituents of many tumors. However, the functions and clinical significance of lncRNAs in tumor-associated macrophages have not been systematically elucidated. In this study, we analyzed the tumor immune microenvironment and lncRNA expression level differences based on The Cancer Genome Atlas (TCGA) and immune cell transcriptome profiles using lung adenocarcinoma microarray datasets GSE3141, GSE51210, GSE37745, and the RNA sequencing data of GSE81089. We then identified a macrophage infiltration-related lncRNA signature (MILnc) including LINC00240, MCF2L-AS1, SFTA3, MIR497HG, FAM215A, UCA1, MIR155HG, and TLRB-AS1 from a list of 147 macrophage-specific lncRNAs. The MILnc was capable of predicting overall survival differences in TCGA and several external validation datasets with a favorable performance. Functional analysis revealed that MILnc was associated with tumor progression and negatively correlated with immune checkpoints. Additionally, MILnc was positively correlated with tumor mutational burden and could predict the immunotherapy response of patients receiving anti-PD-1 or anti-CTLA4 therapy. In summary, our study highlighted the value of MILnc, which revealed the immune environment status and immunotherapy response of lung adenocarcinoma. A robust and powerful MILnc risk model could aid exploration of treatment decisions and mechanisms of macrophage-infiltrating lncRNAs. Highlights: Tumor-associated macrophage abundance was associated with the immune score in LUAD patients. We identified macrophage-specific lncRNAs and constructed an OS risk model named MILnc. The MILnc revealed a predictive value for the immunotherapy response of patients with anti-PD-1 or anti-CTLA4 therapy.